Caracterización de los desechos de la industria brecolera Nintanga, para su reutilización y generación de alimento para cerdos - Albán Rocha, Elin Janeth (2019)
In the present project was investigated how to obtain feed for pigs based on the broccoli excess, in the production company NINTANGA S.A. where the information collected resulted which the company generating around 230 tons of broccoli waste per week; using 80% for composting and the other 20% for sale to the public for the cattle sector next to the factory, being for cattle feed. The first stage of the investigation was the physical-chemical analysis of the waste in its base form made in the laboratory of the Universidad Central del Ecuador, allowing to know the nutritional properties of broccoli waste, the results of the physicochemical characterization, was carried out through a diagram process that determined and made viable the steps for the processing of the feed for pigs, establishing cut, dehydration and grinding criteria. In each criterion, the specification of cuts in tables with measures of 1x1 cm, horizontal slices with 3mm of thickness x 6cm of diameter and vertical slices with3mm of thickness x 4cm of height was experimented; respectively, each cutting experiment being subjected to dehydration at 230º in a given time, obtaining the ideal texture to proceed to grind turning the waste into powder, where the process was performed, the samples were sent to the laboratory for subsequent analyzes submitted to a physical-chemical examination and obtain the nutritional values of the broccoli waste flour, with these data a comparison of product results were obtained by the study is made with the balanced ones for commercialized pigs, establishing that the product is suitable for consumption in the growing pigs